Unexpected occurrence of the genus Eratigena in Laos with description of a new species (Araneae: Agelenidae) - Bolzern, Angelo; Jäger, Peter (Zootaxa, 2015)
During fieldtrips to Laos in 2009 and 2012, two male agelenid specimens were collected from two different caves in the Bolikhamsay Province. Examination of morphological and molecular (CO1) characters revealed, that these specimens belong to a new species, Eratigena laksao sp. n. The cheliceral retromargin of the examined specimens have more than six teeth and the most proximal tooth is distinctly smaller, two character states that are regarded as synapomorphic for Eratigena. Nevertheless, due to the presence of ventral spines at tarsus IV, the completely reduced distal sclerite at the median apophysis, and the lack of females, the genus affiliation of this species remains tentative. E. laksao sp. n. can easily be identified by the unique presence of distinct bristles at the distal palpal tibia.